Vibrational Frequencies of Phosphorus Trichloride with the Vibrational Hamiltonian - Vijayasekhar, J.; Lavanya, K.; Phani Kumari, M.V. (East European Journal of Physics, 2024)
This study presents an approach for precisely determining the stretching vibrational frequencies of the P-Cl bond in phosphorus trichloride (PCl3) using a vibrational Hamiltonian framework that maintains the C3v symmetry point group. Our methodology enables the accurate prediction of vibrational frequencies up to the fifth overtone. It identifies related combination bands, marking a significant advancement in vibrational spectroscopy and molecular modelling. By enhancing the accuracy and depth of our understanding of molecular vibrations, this research paves the way for developing more sophisticated computational models, thereby significantly improving the precision of chemical analyses, and contributing to the broader field of chemical physics.